A critical analysis of language policy in Scotland. Issue 1 (2015) - Phipps, Alison; Fassetta, Giovanna
<x content-type="archive" xml:space="preserve">Abstract</x> Language offerings in Scottish universities are diverse and have their own acute sense of their situation. Some have a precarious hold, others are buoyant. In a research and teaching environment increasingly determined by league tables and "power rankings", this paper considers a variety of insecurities which have manifested themselves in the context of the Gaelic Language Act (Scotland) 2005; in the changing landscape of modern languages, symbolically represented in the university sector; and through the new Curriculum for Excellence for Scottish Schools. In particular, it critically examines some of the less visible aspects and informal forms of language practices which thrive or survive in Scotland today. Drawing theoretically from Cameron (2012), Cronin (2003; 2006; 2012) and Forsdick (2005), and from postcolonial and indigenous scholars of languages, including Tuhiwai Smith (2012) and Muehlmann (2007), the paper considers the legislative environment with regard to language planning in Scotland and offers some theoretical ways forward.